Superoxide Dismutase as an Intervention for Radiation Therapy-Associated Toxicities: Review and Profile of Avasopasem Manganese as a Treatment Option for Radiation-Induced Mucositis - Sonis ST (Dove Medical Press, 2021)
Stephen T Sonis1,2 1Primary Endpoint Solutions, Waltham, MA, 02451, USA; 2Brigham and Women’s Hospital and the Dana-Farber Cancer Institute, Boston, MA, 02215, USACorrespondence: Stephen T SonisPrimary Endpoint Solutions, 360 Second Avenue, Waltham, MA, 02451, USAEmail ssonis@pesclinical.comAbstract: Toxicities associated with radiation therapy are common, symptomatically devastating, and costly. The best chance to effectively mitigate radiation-associated normal tissue side effects are interventions aimed at disrupting the biological cascade, which is the basis for toxicity development, while simultaneously not reducing the beneficial impact of radiation on tumor. Oxidative stress is a key initiator of radiation-associated normal tissue injury as physiologic antioxidant mechanisms are overwhelmed by the accumulation of effects produced by fractionated treatment regimens. And fundamental to this is the generation of superoxide, which is normally removed by superoxide dismutases (SODs). Attempts to supplement the activity of endogenous SOD to prevent radiation-induced normal tissue injury have included the administration of bovine-derived SOD and increasing SOD production using gene transfer, neither of which has resulted in a clinically acceptable therapy. A third approach has been to develop synthetic small molecule dismutase mimetics. This approach has led to the creation and development of avasopasem manganese, a unique and specific dismutase mimetic that, in clinical trials, has shown promising potential to reduce the incidence, severity and duration of severe oral mucositis amongst patients being treated with concomitant chemoradiation for cancers of the head and neck. Further, avasopasem and related analogues have demonstrated mechanism-related antitumor synergy in combination with high dose per fraction radiotherapy, an observation that is also being tested in clinical trials. An ongoing Phase 3 trial seeks to confirm avasopasem manganese as an effective intervention for severe oral mucositis associated with chemoradiation in head and neck cancer patients.Keywords: superoxide dismutase, mucositis, radiation, avasopasem manganese